INDUCTION OF GOJI (LYCIUM BARBARUM) AND UZBEKISTAN GROWING CONDITIONS - Rakhmonberdiyev Shohrukh (International Journal of Human Computing Studies, 2020)
Present, Uzbekistan is one of the fastest growing countries in the world. New innovative innovations are taking place, new ideas and innovations are being created in the field of science. In addition, inter-production is developing and new plant varieties and species are being adapted to our region. There are more than 4,500 species of plants in our region, of which 1,150 are used in folk medicine. Rapidly developed countries such as the United States, European countries, China, and Russia are unable to supply raw materials for the food, pharmaceutical, and perfumery industries. Much of the natural vegetation cover has been reduced. That is why we started to buy medicinal plants that are common in our region (licorice, kovar, kovrak, namatak, sitanhe, etc.) for a large amount of money. Thus, a widespread plantation of medicinal plants is being created in our region. More than 90 species of the lycium family are widespread on Earth, most of which are halophytes. Under natural conditions, this species can be found in the Caucasus, Central Asia, as well as in the Lower Volga region of the European part of Russia. There are 3 naturally occurring species of Lycium in our region and they are called jingil in the vernacular. These are white jungle (L. turkomanicum Turez.), Black jingle (L. ruthenicum Murr.), Wild jungle (L. dasystemum Pojark.) And are found naturally in desert and semi-desert areas. The Lycium family is native to Tibet, China, and is known locally as Goji. It is widely used in Chinese folk medicine and is a world-famous plant.